2021
DOI: 10.1371/journal.pone.0250702
|View full text |Cite
|
Sign up to set email alerts
|

Home birth preference, childbirth, and newborn care practices in rural Peruvian Amazon

Abstract: Home birth is very common in the Peruvian Amazon. In rural areas of the Loreto region, home to indigenous populations such as the Kukama-Kukamiria, birth takes place at home constantly. This study aims to understand the preference for home births as well as childbirth and newborn care practices among Kukama-Kukamiria women in rural Loreto. Following a case study approach, sixty semi-structured, face-to-face interviews were conducted with recent mothers who experienced childbirth within one year prior to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
1
12
0
6
Order By: Relevance
“…On the other hand, the present study showed that women living in rural areas are more likely to have home births, which is consistent with a recent systematic review (24). One possible explanation lies in the fact that pregnant women in rural areas feel fear that their privacy and traditions are not going to be respected in health facilities, and some indicated that they were afraid of being victims of abuse by health professionals (25)(26)(27), which highlights the marked gap between the rural population and health care.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the present study showed that women living in rural areas are more likely to have home births, which is consistent with a recent systematic review (24). One possible explanation lies in the fact that pregnant women in rural areas feel fear that their privacy and traditions are not going to be respected in health facilities, and some indicated that they were afraid of being victims of abuse by health professionals (25)(26)(27), which highlights the marked gap between the rural population and health care.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that these regions are characterized by sociodemographic hurdle, which leads to the inaccessibility of health services (20)(21)(22). According to many authors, other reasons why women in the Peruvian Amazon prefer to have a home birth is the cultural pattern and the lack of cohesiveness with health facilities (23), which is why it is suggested to continue promoting the adequacy of intercultural delivery.…”
Section: Discussionmentioning
confidence: 99%
“…para los controles prenatales, partos y emergencias. Además, notaron que ni la morbilidad ni la mortalidad se reflejaban adecuadamente en los registros oficiales; como si las personas no existieran (8,10).…”
unclassified
“…En el 2015, investigadores de la Universidad Peruana Cayetano Heredia visitaron el río Marañón en la Amazonía peruana, una de las regiones con los peores indicadores de salud materna y neonatal 10 . Junto con la Dirección Regional de Salud (DIRESA) de Loreto, visitaron 13 comunidades en el distrito de Parinari.…”
unclassified
See 1 more Smart Citation